Peatland Wildfire Severity and Post-fire Gaseous Carbon Fluxes - Gray, Alan; Davies, G. Matt; Domènech, Rut; Taylor, Emily; Levy, Peter E. (Ecosystems (New York), 2021)
The future status of peatlands as carbon stores/sinks is uncertain given current and predicted environmental change. Several factors can affect the magnitude of the peatland carbon sink including disturbances such as wildfire. There is at present little evidence of how wildfire affects the emission of carbon dioxide (CO 2 ) and methane (CH 4 ) via perturbation to aerobic and anaerobic respiration. The greatest effects, which are likely to vary according to wildfire severity, would be expected in the immediate post-fire stages when little recovery has taken place. Here, we investigate five UK peatland wildfires (2011–2012) in the immediate post-wildfire period measuring CO 2 and CH 4 fluxes using static chambers. Fire severity was described using a modified form of the composite burn index. A hierarchical partitioning approach indicated time since fire was the most strongly associated variable that fluxes of both CO 2 , and CH 4 followed by soil temperature for CO 2 and fire severity for CH 4 . Using a liner mixed modelling approach to account for repeated measures; fire severity was a significant term for CH 4 and borderline significant for CO 2 . Mean fluxes of CH 4 were consistently lower on burnt sites. In contrast, data from a fire in the north of Scotland appeared to show the opposite relationship for CH 4 with higher fluxes on the burnt sites. These results suggest that wildfire can affect gaseous carbon fluxes, but the responses can be variable in both space and time and that disruption to anaerobic processes may be site and/or fire dependent.